2002
DOI: 10.1590/s0036-46652002000200001
|View full text |Cite
|
Sign up to set email alerts
|

Age-related seroprevalence study for St. Louis encephalitis in a population from Cordoba, Argentina

Abstract: A serological screening was performed in 615 individuals aged 0-87 years, living in the city of Cordoba, Argentina to study the relationship between antibody prevalence for the SLE virus and age. A 13.98% prevalence of neutralizing antibodies was obtained and its relation to age was significantly high (p = 0.045). The highest seroprevalence was noted on individuals over 60 years old (>20%), whereas no subject under 10 was seropositive for this virus. Our results confirm that the agent is endemic in this area a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 9 publications
0
9
1
Order By: Relevance
“…mosquitoes in the province of Santa Fe, including strain 78V6507 (Sabattini et al, 1998). Spinsanti et al (2002) reported a seroprevalence of SLEV antibodies of 13.9% among persons between 0 and 87 years of age living in Córdoba city. The first clinical case of SLEV infection was recorded in Córdoba in the summer of 2002 without additional human cases.…”
Section: Introductionmentioning
confidence: 99%
“…mosquitoes in the province of Santa Fe, including strain 78V6507 (Sabattini et al, 1998). Spinsanti et al (2002) reported a seroprevalence of SLEV antibodies of 13.9% among persons between 0 and 87 years of age living in Córdoba city. The first clinical case of SLEV infection was recorded in Córdoba in the summer of 2002 without additional human cases.…”
Section: Introductionmentioning
confidence: 99%
“…In some regions, SLEV seroprevalence in humans is ≈13% ( 9 ), but the number of documented human infections is small ( 10 ). These findings indicate either that SLEV is more prevalent than reported or that SLEV is reemerging.…”
mentioning
confidence: 99%
“…The distribution of SLEV in Argentina is wide; seroprevalence ranges from 3% to 50% of the country’s population ( 3 ). Spinsanti et al reported results of a serologic screening in persons ages 0–87 years who live in the city of Córdoba; antibodies were most frequently found in persons >60 years of age ( 4 ). However, cases of St. Louis encephalitis reported in Argentina are very rare.…”
mentioning
confidence: 99%